Evaluation of Additional Drosophila suzukii Male-Only Strains Generated Through Remobilization of an FL19 Transgene - Yamamoto, Akihiko; Yadav, Amarish K.; Scott, Maxwell J. (Frontiers in Bioengineering and Biotechnology, 2022)
Drosophila suzukii (Matsumura, 1931, Diptera: Drosophilidae), also known as spotted wing Drosophila, is a worldwide pest of fruits with soft skins such as blueberries and cherries. Originally from Asia, D. suzukii is now present in the Americas and Europe and has become a significant economic pest. Growers largely rely on insecticides for control of D. suzukii. Genetic strategies offer a species-specific environmentally friendly way for suppression of D. suzukii populations. We previously developed a transgenic strain of D. suzukii that produced only males on diet that did not contain tetracycline. The strain carried a single copy of the FL19 construct on chromosome 3. Repeated releases of an excess of FL19 males led to suppression of D. suzukii populations in laboratory cage trials. Females died as a consequence of overexpression of the tetracycline transactivator (tTA) and tTA-activated expression of the head involution defective proapoptotic gene. The aim of this study was to generate additional male-only strains that carried two copies of the FL19 transgene through crossing the original line with a piggyBac jumpstarter strain. Males that carried either two chromosome 3 or a singleX-linked transgene were identified through stronger expression of the red fluorescent protein marker gene. The brighter fluorescence of the X-linked lines was likely due to dosage compensation of red fluorescent protein gene. In total, four X-linked lines and eleven lines with two copies on chromosome 3 were obtained, of which five were further examined. All but one of the strains produced only males on diet without tetracycline. When crossed with wild type virgin females, all of the five two copy autosomal strains examined produced only males. However, the single copy X-linked lines did not show dominant female lethality. Five of the autosomal lines were further evaluated for productivity (egg to adult) and male competition. Based on these results, the most promising lines have been selected for future population suppression experiments with strains from different geographical locations.